Utilization of gum tragacanth as bind enhancing agent in extended restructured mutton chops - Sharma, Heena (J Food Sci Technol, 2013)
Use of extenders in meat products is not only health promoting but can also increase the economic worth of the products. Extension of the meat product is generally associated with poor binding and texture. Thus, the present study was envisaged to solve this problem by the incorporation of gum tragacanth (GT) as bind enhancing agent, used at three different levels viz., 0.1, 0.15 and 0.2 % in a pre standardized formulation of extended restructured mutton chops (ERMC), by replacing the lean meat. The products were subjected to analysis for physico-chemical, sensory and textural properties. There was no significant difference (P > 0.05) in any of the physicochemical property parameters of product incorporated with different levels of GT except fat percent and shear force value. Mean scores for binding, texture and overall acceptability of ERMC incorporated with 0.1 % GT recorded significantly higher value (P < 0.05) than control and other treatment products. On the basis of sensory scores and physico-chemical properties, the optimum incorporation level of GT was adjudged as 0.1 %. Hardness and adhesiveness values were significantly higher (P < 0.05) in product with 0.1 % GT level. The product with optimum level of GT was also assessed for water activity (a(w)) and microbiological characteristics. It was found that treatment as well as control products were quite acceptable up to 15th day of storage period without any marked differences in sensory quality.